Overview of Platelet Counts Before and After Platelet-Rich Plasma (PRP) Preparation - Aisyara Yuliandari; Izah Mahrani; Siska Zafrida; Hartini Hartini; Fauzan Fauzan (Poltekkes Kemenkes Mataram, 2026)
Platelet-Rich Plasma (PRP) is widely utilized in various clinical settings for tissue repair, particularly in skin rejuvenation, scar management, and wound healing. This study aimed to evaluate the profile of platelet counts both prior to and following the PRP preparation process. Whole blood samples were collected from eligible female participants and platelet levels analyzed using a hematology analyzer. The findings revealed a four-fold rise in the mean platelet count, increasing from a baseline of 190.6×103 cells/µL to 781.1×103 cells/μL after preparation. The study concluded that baseline platelet levels in whole blood are directly proportional to the final platelet concentration in PRP.